Microscopic Examination of Ancient and Modern Irrigated Paddy Soils in South Korea, with Special Reference to the Formation of Silty Clay Concentration Features. Issue 4 (30th May 2014) - Lee, H.; French, C.; Macphail, R.I.
ABSTRACT Geoarchaeological investigations of Bronze Age (10th–4th centuries B.C.), early historical (4th–10th centuries A.D.), and premodern to modern paddy soils (11th Century A.D. to contemporary) in South Korea were carried out to understand soil alteration by irrigated rice agriculture. After a review of ancient cultivation micromorphology, especially in the context of wet‐rice agriculture, paddy soils were examined from two archaeological sites, Gulhwa and Pyunggeo, which had been both intermittently occupied since the Bronze Age. This paper highlights anomalous pedofeatures (silty clay concentration features or SCCFs), repeatedly observed in both historical and modern paddy fields, which were studied using soil micromorphology, energy dispersive X‐ray spectrometry (EDS), and microprobe analysis. Results suggest that there are several types of SCCFs, optically distinguishable from other textural pedofeatures. It is concluded that these SCCFs are probably associated with hydromorphic processes, formed under the influence of a tillage and repeated irrigation specific to paddy fields.